Oops-a-Daisy : here comes Maisy! - Dale, Elizabeth; Moore, Natalia ([Sywell] : Igloo Books, 2021)
Everyone loves Maisy, but her clumsiness is driving them crazy! When Maisy drops Honey's birthday present in the cake, she thinks everyone will be angry. Luckily, both Honey and Maisy are in for a very nice surprise.
"The spellbinding story full of fairy fun."--Cover.
Keywords: Fairies -- Juvenile fiction